Vapour-to-liquid nucleation in cone pores. Issue 1 (2nd January 2016) - Li, Jianguo; Liu, Yawei; Jiang, Guangfeng; Zhang, Xianren
Abstract : In this work, we perform a systematic study on the vapour-to-liquid nucleation in a cone pore by using comparatively the classical nucleation theory (CNT) and the constrained lattice density functional theory (constrained LDFT). Three different nucleation scenarios are observed depending on the contact angle θ and apex angle α: the spontaneous phase transition, nucleation with a critical nucleus in Cassie state and nucleation with a critical nucleus in Wenzel state. We also found that both the diagram for nucleation mechanisms and the reduced nucleation barriers with respect to the homogeneous nucleation given by the CNT are at least qualitatively consistent with those from the constrained LDFT. For an increasingly small critical nucleus, the difference between nucleation behaviours from two methods becomes significant due to the macroscopic approximations embedded in CNT, which fails to describe the curvature dependence of surface tension, the line tension effect and the space confinement effect.